Selection of energy efficient path by applying particle swarm optimisation method in wireless sensor networks. (2018) - Al-Humidi, Nada Abdu Omar; Chowdhary, Girish V.
Power and resource limitations of the sensor nodes, the possibility of packet loss and delay are the requirements should be considered while designing routing protocol for the wireless sensor network. To meet and achieve these requirements, several routing techniques have been proposed. Clustering-based routing protocol puts a network structure to satisfy energy efficiency, stability and scalability of the network. In such protocols, the network is organised into clusters in which one node will be selected as a cluster head for the cluster. Selecting cluster head and forming the clusters are the key issues in these protocols, as a result, many routing protocols-based clustering have been proposed. With the objective of solving of these issues, reducing the energy consumption and extending the lifetime of the network, in this paper, energy efficiency-based clustering and particle swarm optimisation (EECPSO) method is proposed. EECPSO performance is evaluated and justified through extensive analysis, comparison and implementation. The results show that the proposed method is highly efficient and effective in term of balancing the consumption of energy and prolonging network lifetime.